AfricArXiv, Diamond Open Access, Sustainability & Funding - Havemann, Jo; Ogot, Madara (My University, 2023)
Presentation held at the II DIAMOND OPEN ACCESS CONFERENCE, October 25 - 26, 2023. Toluca, Mexico Plenary session: Sustainability and funding of diamond open access Capacity building and sustainable finances will be important for the future development of diamond open access. This session discusses how we can further strengthen, sustain, and fund a diamond open access scholarly communication model.
Keywords: Open Access; Sustainability and Funding; African Scholarly Output